2017
DOI: 10.1093/geronb/gbx082
|View full text |Cite
|
Sign up to set email alerts
|

Health Benefits Associated With Three Helping Behaviors: Evidence for Incident Cardiovascular Disease

Abstract: The results demonstrated that specific types of prosocial behavior may be beneficial for women and men. However, tests for effect differences showed that gender did not moderate the relationships between these helping behaviors and CVD risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…Similarly, Chi et al (2021) found that women across the age range were more likely than men to provide unpaid assistance and emotional support. Informal helping and caregiving is normative for women, and although further research is needed, the current findings suggest that gender roles and normative expectations remain stable with age (Burr et al, 2018). Future studies should assess whether gender differences moderate associations between prosocial activities and meso-/macro-level consequences on well-being in older age.…”
Section: Gender Differencesmentioning
confidence: 70%
“…Similarly, Chi et al (2021) found that women across the age range were more likely than men to provide unpaid assistance and emotional support. Informal helping and caregiving is normative for women, and although further research is needed, the current findings suggest that gender roles and normative expectations remain stable with age (Burr et al, 2018). Future studies should assess whether gender differences moderate associations between prosocial activities and meso-/macro-level consequences on well-being in older age.…”
Section: Gender Differencesmentioning
confidence: 70%
“…Here, the potential intersection of age with other social roles and sociodemographic characteristics (e.g., gender) may be important to consider. For example, providing informal help was linked to a lower risk of incident cardiovascular disease in men but not women in the Health and Retirement Study, whereas formal volunteering was associated with lower cardiovascular disease risk in women only (Burr, Han, Lee, Tavares, & Mutchler, 2018). Men tend to provide help that is more discretionary and less taxing (e.g., less direct care) and therefore may show greater well-being benefits from providing assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Men tend to provide help that is more discretionary and less taxing (e.g., less direct care) and therefore may show greater well-being benefits from providing assistance. By contrast, helping others is normative and expected for women; thus, the more discretionary nature of formal volunteering may confer greater benefits than other forms of prosocial activities among women (Burr et al, 2018). Future research could examine whether gender differences in the links between prosocial activities and well-being may differ across the adult life span.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, given the importance of social participation (even in older ages) and the positive outcomes associated with voluntary work (Anderson et al, 2014; Burr, Han, Lee, Tavares, & Mutchler, 2018; Carr et al, 2018), it is crucial to encourage participation among those potentially more in need of these benefits, such as people with health problems. Fostering voluntary work is one aspect of the realization of active aging and social inclusion and becomes possible if there are opportunities to realize individuals’ potential according to their needs, desires, and capacities (Principi, 2014).…”
Section: Discussionmentioning
confidence: 99%